International Conference on Computer Networks and Communication Technologies ICCNCT 2018 - Smys, S.; Bestak, Robert; Chen, Joy Iong-Zong; Kotuliak, Ivan (Lecture Notes on Data Engineering and Communications Technologies, 2019)
The book features research papers presented at the International Conference on Computer Networks and Inventive Communication Technologies (ICCNCT 2018), offering significant contributions from researchers and practitioners in academia and industry. The topics covered include computer networks, network protocols and wireless networks, data communication technologies, and network security. Covering the main core and specialized issues in the areas of next-generation wireless network design, control, and management, as well as in the areas of protection, assurance, and trust in information security practices, these proceedings are a valuable resource, for researchers, instructors, students, scientists, engineers, managers, and industry practitioners. .